The Portrait of Tourism Preference on Ecotourism and Its Impact to Satisfaction: Case in Yogyakarta - Yuniati, Nining (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This research is an exploratory study of the preferences of tourists interested in ecotourism attractions (eco-tourists) in Yogyakarta. Its aim is to map the activities or interests most favored by tourists and whether this leads to satisfaction with their visit. The method used is quantitative with Confirmatory Factor Analysis as a mechanism for selecting tourist preferences, and a regression approach to prove whether these preferences influence tourist satisfaction. The survey was conducted on 221 respondents randomly selected at the visited object locations. The results of the CFA testing revealed that there is a group of pull factors, which are related to everything available at the visited object, and a group of push factors, which are factors related to the tourists’ psychology. Regression testing confirmed that these factors do indeed influence tourist satisfaction